Sibakul Jogja Application Post-Pandemic Yogykarta Government Breakthrough - Ariyanti Luhur Tri Setyarini; Vicki Dwi Purnomo (Formosa Journal of Multidisciplinary Research, 2022)
The Covid 19 pandemic, which began to enter Indonesia since March 2020, has had a significant impact on the sustainability of Micro, Small and Medium Enterprises (MSMEs). The people's economy experienced a significant decline. MSMEs in the Special Region of Yogyakarta that rely on income from the tourism sector and shopping from nomads or immigrants, especially those who are studying, many then close their businesses due to the lack of transactions. The Government's policy that prohibits interaction to reduce the spread of Covid 19 forces the Regional Government to immediately make policy innovations to save the sustainability of MSMEs. This research identified a breakthrough by the Regional Government, in this case the DIY Cooperative and UKM Service in its efforts to save MSMEs, by launching the SiBakul Jogja Program (Information System for Development of Cooperatives and Business Actors in Jogja). What are the opportunities and obstacles in the future. The author conducted this research to provide input for the SiBakul Jogja application as a mainstay of UMKM in DIY. The author uses the interview method and the Secondary Data Analysis method, namely research from various types of documents such as books. The results of the study show that the existence of SiBakul has helped SMEs a lot to survive in the pandemic era, and even then "levelled up" in sales and marketing of their products, but there are still a number of things that need to be improved and perfected to make them more effective.